Learning strategies applied by online learners of the Open University of Malaysia / Haziah Jamaludin, Fuziah Sulaiman and Sabariah Arbai - Jamaludin, Haziah; Sulaiman, Fuziah; Arbai, Sabariah (Institute of Education Development (InED), 2007)
Online courses and distance learning programs are now offered at most of our universities. One of the factors that will lead to successful student learning in these two modes is the ability to use appropriate learning strategies. Awareness towards the understanding and the use of appropriate strategies is important for the students' survival in the program. Using a qualitative approach this study examined the strategies of the undergraduate students of the Open University of Malaysia. The data analysis revealed that the adult online learners used strategies, which were categorized into five themes - Use of Memory Tools, Planning and Awareness, Visual Organizers, Re-enforcement strategies and Seeking Assistance. From the information obtained the study concludes with suggestions for the e-learning provider.